THE SCHOLARLY PERSONA IN DAGESTANI ARABIC BIOGRAPHICAL LITERATURE - Sihaliev, Samil' Sihalievic (History, Archeology and Ethnography of the Caucasus, 2025)
This article explores the construction of scholarly personae in 20th-century Arabic biographical and hagiographical literature from Daghestan. Drawing on the conceptual framework of persona as formulated by Mineke Bosch and further developed by Herman Paul, the study treats persona not as a fixed social role or stereotype, but as a culturally embedded repertoire of scholarly virtues, practices, and dispositions. Paul’s tripartite model – micro, meso, and macro levels of scholarly identity – serves as a useful heuristic, though this article privileges the meso-level: the articulation of time- and place-specific ideals of scholarly subjectivity. However, the Daghestani case reveals that such models are often shaped less by institutional norms than by ethical preferences, such as the valorisation of Sufi piety, legal expertise, or rational inquiry.Through close textual analysis of four key Arabic works – Nuzhat al-adhhān by Nadhīr al-Durgilī, Tarājim ‘ulamā’ Dāghistān by ‘Alī Kaiaev, Ṭabaqāt al-khwājagān by Shu’ayb al-Bāghinī, and Sirāj al-sa’ādāt by Ḥasan al-Qaḥī – the article demonstrates the plural and contested nature of scholarly ideals in Daghestani Islam. Al-Durgilī constructs a harmonised model of the ideal Muslim scholar, while Kaiaev adopts a critical stance, selectively praising or censuring figures based on rationalist or ethical criteria. Sufi authors such as al-Bāghinī and al-Qaḥī frame scholarly legitimacy around spiritual charisma, ecstatic experience, and miracles.
Keywords: scholarly persona; Islamic biographical literature; Dagestan; hagiography; intellectual history; Islamic manuscript culture